PENINGKATAN KETUNTASAN DAN HASIL BELAJAR SISWA KELAS X MIPA 1 SMA NEGERI 1 NUSA PENIDA PADA MATA PELAJARAN PKN MELALUI PENERAPAN MODEL PEMBELAJARAN BERBASIS PORTOFOLIO - I Wayan Soma (Universitas Panji Sakti, 2022)
AbstractStudent motivation, particularly in Civics subject today, requires special attention due to learning motivation is an important factor in supporting the success of the student learning process, which can be seen from the increased mastery and student learning outcomes. Therefore, student learning motivation must be maintained properly therefore it will be easier for teachers to guide and direct students in the Civics learning process. Based on the initial observation data, it was known that the Civics learning process, especially in class X MIPA 1 students at SMAN 1 Nusa Penida was still teacher centered and less attractive, resulting in students becoming less interested in participating in the entire Civics learning process. In order to improve completeness and learning outcomes of Civics subjects, an appropriate learning model was needed. One learning model that is considered appropriate to be used as an alternative way of active student learning is by using a portfolio-based learning model which was implemented in the odd semester of the Academic Year 2019/2020. Through the application of this portfolio-based learning model students were invited to identify and carry out scientific analysis of strategic issues that were currently developing in society and provide an alternative solution to problem solving. Thus, it is expected that in the future students will obtain various benefits both from an academic standpoint and social interaction. Based on the results of the research that has been done, it was obtained that there was an increase in completeness and student learning outcomes when this portfolio-based learning model was applied. In cycle I, it can be seen that classically the percentage of students who were declared to have completed learning reached 26.5%, then in cycle II there was an increase in the percentage of learning completion to 80.5%, and there was another increase in cycle III to 98.8%. The average student learning outcomes also experienced a significant increase which in cycle I the average student learning outcomes was 55.6, and then in cycle II it increased to 75.5 and increased again in cycle III to 88.45.Keywords: Portfolio-Based Learning Model, Learning Outcomes, learning completeness